The factors that affect transfer of training among supporting unit staff in Human Resource Department at Majlis Amanah Rakyat (MARA) Kuala Lumpur / Noor Zakiah Khairuzzaman - Khairuzzaman, Noor Zakiah (Faculty of Business and Management, 2011)
The aim of this study is to examine the factors that affect transfer of training among supporting unit staff. Quantitative method through questionnaire survey was used for data collection in which questionnaires were distributed to 76 respondents in the Department of Human Resource, Majlis Amanah Rakyat, Kuala Lumpur. In the last part, this research will determine whether factors that affect transfer of training such as Training Design, Trainee’s Characteristics and Work Environment will affect transfer of training or not. By using all of the 76 Questionnaires, the findings highlighted on the three factors that affect transfer of training as mentioned. Therefore, in order to determine the relationship between transfer of training and factors that affect transfer of training, a Likert-type scale has been developed and tested. Therefore, in this research, the researcher tries to identify the most influential factor and the relationship between dependant and independent variables. Information obtained could be practical when management decides to analyze the transfer of training elements that has been addressed in this study as to get management support and to create conducive environment to apply related skill and knowledge on the job.